2018
DOI: 10.1152/ajpregu.00057.2018
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive index of cardiac autonomic control based on time-varying respiration derived from ECG

Abstract: Frequency-domain indices of heart rate variability (HRV) have been used as markers of sympathovagal balance. However, they have been shown to be degraded by interindividual or task-dependent variability, and especially variations in breathing frequency. The study introduces a method to analyze respiration-(vagally) mediated HRV, to better assess subtle variations in sympathovagal balance using ECG recordings. The method enhances HRV analysis by focusing the quantification of respiratory sinus arrhythmia (RSA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…These confounding factors make it more challenging to distinguish ictal patterns from non-ictal ones, resulting in lower accuracy [ 48 ]. Also, similar activation of the autonomic nervous system can occur before physiological arousal or other sleep-related movements [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…These confounding factors make it more challenging to distinguish ictal patterns from non-ictal ones, resulting in lower accuracy [ 48 ]. Also, similar activation of the autonomic nervous system can occur before physiological arousal or other sleep-related movements [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory rates were determined via chest belt as well as calculated from the ECG registration as previously described [12,13]. Corresponding hardware and software were included in the HRV-Scanner (Biosign ® ).…”
Section: Measurements Of Respiratory Ratesmentioning
confidence: 99%
“…The results showed that the multiscale features obtain a better mental workload recognition effect. In [15], the respiratory and HRV signals were extracted using 5 min scale electrocardiogram (ECG) signals. This study introduced a novel method that fused respiratory and HRV signals to assess subtle variations in sympathovagal balance using ECG recordings during the MATA-II mission.…”
Section: Introductionmentioning
confidence: 99%